Isolated primary Hydatid cyst of kidney: A case report of asymptomatic patient - Gavit, Sangita M.; Ahirrao, Bhagyashri M.; Ahirrao, Mahesh H.; Dravid, Nandkumar V. (Journal of Medicine and Health Sciences Research, 2019)
We report an isolated primary hydatid cyst of kidney in a pregnant asymptomatic woman. We also present salient diagnostic feature of asymptomatic patients of hydatid cyst.